2015
DOI: 10.1007/s12020-015-0555-4
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic alterations in human parathyroid tumors

Abstract: Epigenetics alterations are involved in tumorigenesis and have been identified in endocrine neoplasia. In particular, DNA methylation, microRNAs deregulations and histone methylation impairment are detected in tumors of the parathyroid glands. Parathyroid tumors are the second most common endocrine neoplasia following thyroid cancer in women, and it is associated with primary hyperparathyroidism, a disease sustained by PTH hypersecretion. Despite the hallmark of global promoter hypomethylations was not detecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 53 publications
0
42
0
Order By: Relevance
“…When compared to normal parathyroid tissue, parathyroid neoplasms were shown to have aberrant hypermethylation of tumour suppressor genes in Wnt/β-catenin signalling ( APC, SFRP1, SFRP2, SFRP4 ), cyclin D1 signalling ( CDKN2A, CDKN2B ), as well as WT1, RIZ1, RASSF1A and HIC1 141 152 205 210–213. As mentioned previously, cyclin D1 signalling plays an important role in cell cycle progression in parathyroid tissue and can be induced by Wnt/β-catenin signalling, another tumorigenesis pathway in many solid tumours 81 141 196 212 214–216 . APC, SFRP1, SFRP2 and SFRP4 genes all serve important regulatory functions in Wnt/β-catenin signalling, whereas CDKN2A and CDKN2B genes appear to regulate cyclin D1 signalling 81 141 212 214–216 .…”
Section: Pathogenesis and Molecular Genetics Of Hptmentioning
confidence: 99%
See 2 more Smart Citations
“…When compared to normal parathyroid tissue, parathyroid neoplasms were shown to have aberrant hypermethylation of tumour suppressor genes in Wnt/β-catenin signalling ( APC, SFRP1, SFRP2, SFRP4 ), cyclin D1 signalling ( CDKN2A, CDKN2B ), as well as WT1, RIZ1, RASSF1A and HIC1 141 152 205 210–213. As mentioned previously, cyclin D1 signalling plays an important role in cell cycle progression in parathyroid tissue and can be induced by Wnt/β-catenin signalling, another tumorigenesis pathway in many solid tumours 81 141 196 212 214–216 . APC, SFRP1, SFRP2 and SFRP4 genes all serve important regulatory functions in Wnt/β-catenin signalling, whereas CDKN2A and CDKN2B genes appear to regulate cyclin D1 signalling 81 141 212 214–216 .…”
Section: Pathogenesis and Molecular Genetics Of Hptmentioning
confidence: 99%
“…As mentioned previously, cyclin D1 signalling plays an important role in cell cycle progression in parathyroid tissue and can be induced by Wnt/β-catenin signalling, another tumorigenesis pathway in many solid tumours 81 141 196 212 214–216 . APC, SFRP1, SFRP2 and SFRP4 genes all serve important regulatory functions in Wnt/β-catenin signalling, whereas CDKN2A and CDKN2B genes appear to regulate cyclin D1 signalling 81 141 212 214–216 . WT1 (Wilms tumour 1) encodes an important transcription factor for cellular development and survival, and mutations in WT1 have been linked to various solid tumours 81 141 210 212.…”
Section: Pathogenesis and Molecular Genetics Of Hptmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene alterations between benign parathyroid adenomas and parathyroid carcinomas have been identified [20]. Large-scale epigenetic studies have demonstrated repression of miRNAs in PC tissue relative to normal parathyroid glands as well, arguing that further studies in epigenetic deregulation of parathyroid tumors may provide new strategies for treatment [21].…”
Section: Geneticsmentioning
confidence: 99%
“…To date, the incidence of thyroid carcinoma is still on the rise for uncertain reasons. Some researchers have supposed that it might be associated with epigenetic events 3, 4, 5. As THCA recurrence is a common event in thyroid carcinoma patients, especially in the early stage 6, 7.…”
Section: Introductionmentioning
confidence: 99%